Integrated Batch Production and Multiple Preventive Maintenance Scheduling on A Single Machine to Minimize Total Actual Flow Time. (August 2019) - Yusriski, R; Astuti, B; Ilham, M; Zahedi
Abstract: We discuss the problem of batch production and multiple preventive maintenance (PM) scheduling on a single machine. On batch production systems, there is a situation that PM activity should be executed at the time when the machine is processing the parts on a batch. Delaying that action could cause an increase in the possibility of a rejected product. However, applying the PM action would interrupt the process and also need an additional setup when starting the process again. It could impact the longer total flow time. This research proposed two algorithms (the optimal and the heuristic algorithm) which integrated both of batch production and multiple preventive maintenance schedules. The performance of the algorithm measured by minimizes the total actual flow time. Experimental results show that the effectivity of the heuristic algorithm is between 66% until 100% from the optimal algorithm.